Self‐Aggregating Tau Fragments Recapitulate Pathologic Phenotypes and Neurotoxicity of Alzheimer's Disease in Mice - Ly Thi Huong Luu Le; Jeeyoung Lee; Dongjoon Im; Sunha Park; Kyoung‐Doo Hwang; Jung Hoon Lee; Yanxialei Jiang; Yong‐Seok Lee; Young Ho Suh; Hugh I. Kim; Min Jae Lee (Advanced Science, 2023)
Abstract In tauopathy conditions, such as Alzheimer's disease (AD), highly soluble and natively unfolded tau polymerizes into an insoluble filament; however, the mechanistic details of this process remain unclear. In the brains of AD patients, only a minor segment of tau forms β‐helix‐stacked protofilaments, while its flanking regions form disordered fuzzy coats. Here, it is demonstrated that the tau AD nucleation core (tau‐AC) sufficiently induced self‐aggregation and recruited full‐length tau to filaments. Unexpectedly, phospho‐mimetic forms of tau‐AC (at Ser324 or Ser356) show markedly reduced oligomerization and seeding propensities. Biophysical analysis reveal that the N‐terminus of tau‐AC facilitates the fibrillization kinetics as a nucleation motif, which becomes sterically shielded through phosphorylation‐induced conformational changes in tau‐AC. Tau‐AC oligomers are efficiently internalized into cells via endocytosis and induced endogenous tau aggregation. In primary hippocampal neurons, tau‐AC impaired axon initial segment plasticity upon chronic depolarization and is mislocalized to the somatodendritic compartments. Furthermore, it is observed significantly impaired memory retrieval in mice intrahippocampally injected with tau‐AC fibrils, which corresponds to the neuropathological staining and neuronal loss in the brain. These findings identify tau‐AC species as a key neuropathological driver in AD, suggesting novel strategies for therapeutic intervention.